The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1002/pola.22826
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of controlled‐structure primary amine‐based methacrylamide polymers via the reversible addition‐fragmentation chain transfer process

Abstract: We report here a novel direct method for the syntheses of primary aminoalkyl methacrylamides that requires mild reagents and no protecting group chemistry. The reversible addition‐fragmentation chain transfer polymerization (RAFT) of the aminoalkyl methacrylamide revealed to be highly efficient with 4‐cyanopentanoic acid dithiobenzoate (CTP) as chain transfer agent and 4,4′‐azobis(4‐cyanovaleric acid) (ACVA) as initiator. Cationic amino‐based homopolymers of reasonably narrow polydispersities (Mw/Mn < 1.30) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 41 publications
0
92
0
Order By: Relevance
“…Recently, several groups have reported that the polymerization of monomers with primary amine functionality (273)(274)(275)(276) (Table 16) can be effectively controlled with the monomer as the ammonium salt and with no or minimal loss of the RAFT end-group. [90,152,153,166] Some of the more exotic monomer subjected to RAFT polymerization are included in the tables that follow. They include methacrylates (Table 17), acrylates (Table 18), methacrylamides (Table 19), acrylamides derived from amino acids (Table 20), other acrylamides (Table 21), St derivatives (Table 22), and vinyl monomers (Table 23) Table 20).…”
Section: Raft Polymer Synthesesmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, several groups have reported that the polymerization of monomers with primary amine functionality (273)(274)(275)(276) (Table 16) can be effectively controlled with the monomer as the ammonium salt and with no or minimal loss of the RAFT end-group. [90,152,153,166] Some of the more exotic monomer subjected to RAFT polymerization are included in the tables that follow. They include methacrylates (Table 17), acrylates (Table 18), methacrylamides (Table 19), acrylamides derived from amino acids (Table 20), other acrylamides (Table 21), St derivatives (Table 22), and vinyl monomers (Table 23) Table 20).…”
Section: Raft Polymer Synthesesmentioning
confidence: 99%
“…In the case of bis-RAFT agents sequential polymerization of two monomers will yield a triblock. [269] BA [270] MA [270] NIPAM [269,[271][272][273] 420 [274] BA [281] DA [281] St [71,275] 2VP [276] NVP [103] NIPAM/274 [153] DEHEA [280] MA [281] TMAPMA/PEGMA/NIPAM [277] (PEGMA/320) [165] tBA [280] BA/AA [279] (PEGMA/344) [165] 331 [159] AEMA/325/328 [278] DEHEA-b-ODA [280] DMAM-b-331 [159] DMAM-b-331-b-NIPAM [159] DEHEA-b-tBA [280] NIPAM-b-DMAM [272] 2VP-b-EA [276] tBA-b-DEHEA [280] AEME/328/342 [278] 105 [282] [282] PEGA-b-St [282] 106 [188] [188] EHA-b-MA [188] S S S…”
Section: *mentioning
confidence: 99%
See 2 more Smart Citations
“…AEMA hydrochloride was synthesized according to a reported mild and protecting-group-free method with slight modifications. 38 Ethylenediamine (16 mL, 239 mmol) in MeOH (100 mL) was added to a stirred solution of ethylenediamine hydrochloride (30 g, 226 mmol) in distilled water (100 mL) at 0°C. The resulting mixture was stirred for 1 h. Methacrylic anhydride (68 mL, 459 mmol) and a few crystals of hydroquinone in MeOH (50 mL) were subsequently added dropwise to the reaction mixture.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%